Nationwide Analysis of Dog Bite Injuries: Different Age Groups, Different Injury Patterns. Issue 10 (October 2021) - Tam, Benjamin; Matsushima, Kazuhide; Chiba, Hiroto; Park, Timothy; Slocum, Charles; Lam, Lydia; Inaba, Kenji; Demetriades, Demetrios
Background: As the number of households with dogs in the United States has increased, so has the incidence of dog bites. Contemporary analysis of nationwide epidemiological data regarding such injuries is scarce. The purpose of this study is to describe dog bite injury patterns and related surgical interventions with a focus on differences between pediatric and adult age groups. Study Design: This is a retrospective study (2015-2017) using the National Trauma Data Bank. 10 569 patients were included. Results: Of these, 4729 (44.7%) qualified as pediatric (age ≤ 12 years) and 5840 (55.3%) qualified as adults (age ≥ 13 years). Pediatric patients were more frequently admitted with facial injuries (78.1% vs. 29.3%, P < .01) and facial fractures (4.8% vs. 2.5%, P < .01), and had a higher incidence of facial bone surgical procedures (1.3% vs. .5%, P < .01). Adult patients were more frequently admitted with upper extremity injuries (65.8% vs. 21.2%, P < .01) and upper extremity vascular arterial injuries (2.3% vs. .2%, P < .01) with a higher incidence of upper extremity arterial procedures (1.3% vs. .2%, P < .01). Conclusion: This study demonstrates the contrast in injury patterns from dog bite between adults and children. These findings can dictate injury prevention policies and prepare clinicians to treat dog bite victims.